“Silence and hoarseness”: Symbolic poetics and linguistic structures in the music of Bob Dylan and Trịnh Công Sơn – an interdisciplinary approach - Pham, Hang Thu; Nguyen, Nhung Thi My (Edelweiss Applied Science and Technology, 2025)
This study offers a comparative analysis of the lyrical aesthetics of Bob Dylan and Trịnh Công Sơn—two iconic songwriter-poets shaped by distinct cultural and historical milieus. The primary aim is to explore how both artists construct symbolic meaning through language, moving beyond conventional communicative functions to evoke deeper emotional, cognitive, and spiritual dimensions. Methodologically, the research adopts an interdisciplinary framework that integrates semiotics, poetics, and linguistic aesthetics. Through close reading and symbolic analysis, the study examines the role of metaphor, binary oppositions, rhythm, and intertextuality in shaping each artist’s lyrical world. Findings indicate that despite their divergent aesthetic orientations—Dylan articulating protest through fractured, disruptive language, and Trịnh evoking transcendence through restraint and meditative stillness—both artists reimagine language as a vessel of emotional embodiment and ethical resonance in art. Ultimately, the study positions song lyrics as multilayered cultural texts and proposes a model for cross-cultural poetics within the evolving discourse of interdisciplinary humanistic inquiry.